Mortality due to COVID-19 during the pandemic: A comparison of first, second and third SMAtteo COvid19 REgistry (SMACORE). Issue 2 (February 2022) - Zuccaro, Valentina; Colaneri, Marta; Asperges, Erika; Valsecchi, Pietro; Sambo, Margherita; Maiocchi, Laura; Sacchi, Paolo; Muzzi, Alba; Musella, Valeria; Cutti, Sara; Rettani, Marco; Mojoli, Francesco; et al.
Abstract: COVID-19 tide had shattered on European countries with three distinct and tough waves, from March and April, 2020; October and November, 2020 and March and April, 2021 respectively. We observed a 50% reduction in the hazard of death during both wave II and III compared with wave I (HR 0.54, 95%CI 0.39–0.74 and HR 0.57, 95%CI 0.41–0.80, respectively). Sex and age were independent predictors of death. We compare in-hospital mortality of COVID-19 patients admitted at our Referral Hospital of Northern Italy during the different waves, discuss the reasons of the observed differences and suggest approaches to the challenges ahead. Abstract : Covid-19; In-hospital mortality.